Zahida Ibrahim, the pioneer of libraries in Iraq - Ashoor, Leqaa Amer (Al-Adab Journal, 2022)
Indexing and librarian expert, she was born in Baghdad (1926) and graduated from the College of Law at the University of Baghdad in (1949). After her graduation, she worked as a librarian at the Higher Teachers House (1949-1958). She was able to obtain the first fellowship in the field of libraries by UNESCO in (1953). One of the founders of the Central Library at the University of Baghdad. She gave many scientific lectures in the field of libraries, and she was chosen from the most prominent library personalities by UNESCO in order to issue an Arabized version of the Doy Classification, which has a number of books, including five manuscript books in the science of libraries. Her philosophy: (There is no good in a book that does not read), she dedicated all her books to the Central Public Library and to other libraries.